Nonlocal voltage in a spin field effect transistor with finite channel width - Eom, Jonghwa; Koo, Hyun Cheol; Chang, Joonyeon; Han, Suk Hee (Current applied physics, 2011)
Spin transport in the two-dimensional electron gas with strong spin–orbit interaction is examined by using a simple phenomenological simulation. The large spin–orbit interaction and the randomized electron trajectory due to the impurity scattering make the nonlocal voltage of a spin field effect transistor undetectable in the diffusive regime. However, the spin-precessional phase accumulates coherently in the ballistic regime and the nonlocal voltage is given by a function of spin–orbit interaction parameter. If the distance between injector and detector is comparable to the mean free path, a sinusoidal oscillation of nonlocal voltage is restored even for a wide channel.